2015
DOI: 10.3171/2015.2.spine141118
|View full text |Cite
|
Sign up to set email alerts
|

Clavicle pain and reduction of incisional and fascial pain after posterior cervical surgery

Abstract: OBJECT Incisional pain after posterior cervical spine surgery can be severe and very unpleasant to the patient. Ongoing incisional pain is one of the key disadvantages of posterior over anterior surgical approaches to the cervical spine. It prolongs hospital stays and delays return to work. In this study, the hypothesized that incisional pain in the immediate postoperative period is caused partially by tension on the skin as well as on the deep cervical fascia and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Lastly, one study discussed the use of clavicle bracing after posterior cervical or cervicothoracic decompressions and/or decompressions with fusions. 11 This study suggested that clavicle bracing may reduce acute postoperative pain and medication requirements, but the impact of cervical bracing was not assessed. This study did not assess fusion rates.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Lastly, one study discussed the use of clavicle bracing after posterior cervical or cervicothoracic decompressions and/or decompressions with fusions. 11 This study suggested that clavicle bracing may reduce acute postoperative pain and medication requirements, but the impact of cervical bracing was not assessed. This study did not assess fusion rates.…”
Section: Discussionmentioning
confidence: 91%
“…Duetzmann et al 11 looked at degenerative conditions of the cervical spine that required posterior cervical single or multi-level decompressions, with or without fusions, as well as posterior cervicothoracic decompressions and fusions. A total of 30 patients were included in the study; 15 patients, whose average age was 55 years, were not placed in clavicle brace in the postoperative period, and 15 patients, whose average age was 57 years, were braced postoperatively with a clavicle brace for 30 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When operating between the cervical and upper thoracic spine, these predispositions may act in concert with the unique anatomy of the cervicothoracic spine by further increasing the risk for wound dehiscence. Surgical wounds over the cervicothoracic spine are more susceptible to mechanical stress such as pressure and tension around the wound boarders, but also on the fascia due to high tensile and traction forces of the trapezius muscle [ 15 ]. Also, postoperative paraspinal muscle atrophy around the cervicothoracic junction will often lead to relatively more prominent spinous processes and implants compromising already poor skin conditions, especially in elderly patients.…”
Section: Discussionmentioning
confidence: 99%